THE RELATIONSHIP OF LACTATE-ALBUMIN RATIO TO MORTALITY AND LENGTH OF STAY IN SEPSIS PATIENTS AT ICU DR. SARDJITO GENERAL HOSPITAL - Pasmawati, Desti; Wisudarti, Calcarina Fitriani Retno; Adiyanto, Bowo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2024)
Background : Sepsis is one of the causes of morbidity and mortality patients hospitalized in the intensive care unit (ICU) which requires early detection and management to predict outcomes. An increase in lactate together with decrease in albumin is encountered in severe inflammatory states. Lactate-albumin ratio has a predictive value of mortality in patient with sepsis that is similar to APACHE II and SOFA scores. These biomarkers can be done quickly, affordable, and available in many hospitals in Indonesia. Objective : To determine the relationship between the lactate-albumin ratio and mortality and length of stay patient with sepsis in ICU of Dr. Sardjito Hospital. Method : Research design using a retrospective cohort observational study method by collecting data from the medical records of sepsis patients treated at ICU of Dr. Sardjito Hospital. Data on lactate and albumin in plasma levels at admission and mortality events were collected to calculate the optimal cutoff using the ROC curve. The relationship between lactate-albumin ratio levels and mortality was analyzed using the chi-square test method followed by logistic regression in multivariate analysis. Results : The total study subjects were 136 patients, wuth a median age of 55 years. The cut-off value for the Lactate-Albumin ratio in predicting mortality was found to be 0,878, with a sensitivity of 73.0 % and a specificity of 57.1% (AUC = 0,687; 95% CI 0,56-0,81; p=0,007). The cut-off value for the Lactate-Albumin ratio in predicting ICU length of stay was found to be 0,878, sensitivity 71,2% and specificity 63,6% (AUC = 0,684; 95% CI 0,53-0,84; p=0,043). Multivariate analysis showed that an increase in the Lactate-Albumin ratio was an independent and significant factor as a predictor of mortality (OR=3,43; 95% CI 1,29-9,16; p=0,013) and ICU length of stay (OR=4,33; 95% CI 1,19-15,68; p=0,036). Age, sex, hypertension, diabetes mellitus, cancer, obesity, and cerebrovascular disease were not independently associated with mortality dan ICU length of stay. Conclusion : An increase in the Lactate-Albumin ratio is independently and significantly associated with an increased risk of mortality and length of stay in sepsis patients.